PENGARUH PENGETAHUAN DAN SIKAP PADA PRAKTIK MENYUSUI : STUDI LITERATUR - Handayani, Lina; Kosnin, Azlina Md; Jiar, Yeo Kee (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2010)
The knowledge and attitude are very importantfor successful breastfeeding practice. This paper reports a systematic literature review about influenceof knowledge and attitude on beastfeeding practice around the world. An online literature search was conducted in Science Direct, Cochrane Database of synstematic reviews, PubMed, WileyInterScience, SpringerLink, and Garuda. Almost all of studies show the similar result; knowledge and attitude influence breastfeeding practice.